2022
DOI: 10.1128/spectrum.01802-22
|View full text |Cite
|
Sign up to set email alerts
|

The Threat of Potentially Pathogenic Bacteria in the Feces of Bats

Abstract: Bats are one of the most diverse and widely distributed groups of mammals living in close proximity to humans. In recent years, bat-borne viruses and the viral zoonotic diseases associated with bats have been studied in great detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…Compared with viruses, there are few studies on the microorganism carried by bats, particularly the reports of new bacterial species that are straightforward to be neglected ( Muhldorfer, 2013 ). Our laboratory has investigated the intestinal and fecal flora of bats since 2018 to identify potentially pathogenic microbial species and dissect the process of disease transmission ( Huang et al., 2022c ). So far, we have published over ten new species of bacteria isolated from bat feces, among which Brevibacterium zhoupengii ( Huang et al., 2022a ), Microbacterium fandaimingii ( Zhou et al., 2021 ), Gordonia zhenghanii , G. liuliyuniae ( Huang et al., 2022b ), Tomitella gaofuii and T. fengzijianii ( Huang et al., 2022d ) belong to the phylum Actinobacteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with viruses, there are few studies on the microorganism carried by bats, particularly the reports of new bacterial species that are straightforward to be neglected ( Muhldorfer, 2013 ). Our laboratory has investigated the intestinal and fecal flora of bats since 2018 to identify potentially pathogenic microbial species and dissect the process of disease transmission ( Huang et al., 2022c ). So far, we have published over ten new species of bacteria isolated from bat feces, among which Brevibacterium zhoupengii ( Huang et al., 2022a ), Microbacterium fandaimingii ( Zhou et al., 2021 ), Gordonia zhenghanii , G. liuliyuniae ( Huang et al., 2022b ), Tomitella gaofuii and T. fengzijianii ( Huang et al., 2022d ) belong to the phylum Actinobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the fecal microbiota in bats was found to be diverse with predominant bacterial phylum Proteobacteria and Firmicutes ( Sun et al., 2020 ; Huang et al., 2022c ). The presence of opportunistic pathogens Citrobacter freundii , Escherichia coli , Enterococcus faecalis , Serratia fonticola, Shigella flexneri , and Rahnella aquatilis were also recorded ( Muhldorfer, 2013 ; Wolkers-Rooijackers et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the identity of the suspected/confirmed human pathogen depends on the excreta type, which has implications for disease transmission to humans. Another study using PacBio sequencing in the faeces of Chinese bats identified 480 species-level phylotypes (SLP), of which 32 were known human pathogens, while another 40 were flagged as potential human pathogens [ 62 ]. Monitoring of bacterial metagenomes shed in bats’ saliva, urine, and faeces may enable the surveillance and early detection of zoonotic pathogens.…”
Section: The Uniqueness Of Bat Gut Microbiomesmentioning
confidence: 99%
“…This is a notable divergence from the shorter read lengths associated with other sequencing techniques, e.g., on the V4 region of 16S rRNA gene. To the best of our knowledge, only two previous microbiota studies on bats and none on wild birds have used long read sequencing, i.e., PacBio study in China 14 and Oxford Nanopore study in Spain 15 . In addition to PacBio approach, we used traditional gene-targeted PCR with Sanger sequencing to elaborate the bacterial species-specific data.…”
mentioning
confidence: 99%